Peran Orang Tua dalam Membantu Anak Usia Sekolah Dasar Mengasah Keterampilan Berbahasanya - Magdalena, Ina; Fauziah, Asika; Mayanti, Hani Melly; Yuniawan, Nurmanita; Milawati, Siti Santi (YASIN, 2022)
Skill comes from the word skilled, which means proficient in completing tasks, capable and agile. Skill itself is defined as a skill to complete the task. Reber in Muhibbin2 2008, skill is the ability to perform patterns of behavior that are complex and neatly arranged smoothly and in accordance with circumstances to achieve certain results. Skills include not only motor movements but also the embodiment of cognitive mental functions. The connotation is broad so that it comes to influencing or utilizing other people. This means that people who are able to utilize other people appropriately are also considered skilled people. Examples of skills are language skills and math skills. Language skills are one of the skills that need to be mastered by everyone, so that by being skilled at speaking a person's insight into thinking will become wider. A person's ability to express his thoughts will be seen when conveying it through communication, both oral and written. Basically everyone has the desire to say something, such as explaining, describing. Language skills consist of listening, speaking, reading, and writing.